Tadhkira-yi Muqīm-i khānī : Sayr-i tārīkhī, farhangī u ijtimāʿi-yi Mā warāʾ al-nahr dar ʿahd-i Shībāniyān u Ashtarkhāniyān - Munshī, Muḥammad, (Miras Maktoob, ISBN: 9789004365452., 2019)
Throughout history, the lands of Central Asia have seen empires come and go. A case in point is Transoxania, a region roughly situated between the Oxus and Jaxartes rivers. After the death of Genghis Khan in 1227, Transoxania became part of the Chagatai khanate, following which it was first ruled by the Timurids and then by the Shibanids and the Janids (Ashtarkhanids) as the khanate of Bukhara. At the beginning of the 18th century, Janid power over the khanate of Bukhara had declined to the point that a local leader called Muḥammad Muqīm Bahādur Khān (d. 1119/1707) declared himself independent in Balkh in 1114/1702. His reign was short-lived and he was summarily executed in 1119/1707. The present volume describes the history of the Shibanids, the Janids and the coming-to-power of Muqīm Bahādur Khān until the year 1116/1704. Its author, Bahādur's secretary Muḥammad Munshī, intended to write a sequel, which has, however, never been found.